GAMBARAN MENGENAI STATUS KEBERSIHAN GIGI DAN MULUT SERTA KEMANDIRIAN TOILET TRAINING PADA ANAK TUNAGRAHITA - Gasik Prawestri; Elis Hartati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2019)
Children with intellectual disabilities are one type of disabilities that frequently occur in Indonesia. The total number of children with intellectual disabilities in Semarang based on the data of poor citizens’ management information system (SIMGAKIN) in 2012 is 667 children. The condition of children with intellectual disabilities that occurs will result in a lack of self-care in maintaining health. Self-care such as good dental and oral hygiene status and toilet training independence is needed to deal with the problems of children with intellectual disabilities. The purpose of this study is to describe the dental and oral hygiene status and toilet training independence in children with intellectual disabilities. The research method used is descriptive with the quantitative method. The sampling technique used is a total sampling of 55 respondents. Retrieving data using OHI-S inspection sheet for dental and oral hygiene status and independence questionnaire for toilet training. The results showed that the depiction of the dental and oral hygiene status of children with intellectual disabilities in the category of good is 43.6%, medium is 50.9%, and poor is 5.5%, while the toilet training independence in the category of independent is 21.8%, less independent is 50.9%, and total dependence is 27.3 %. Schools are expected to facilitate the implementation of the program to maintain and improve self-care on dental and oral hygiene and independence in toilet training.